Effect of AISI H13 Steel Substrate Nitriding on AlCrN, ZrN, TiSiN, and TiCrN Multilayer PVD Coatings Wear and Friction Behaviors at a Different Temperature Level - Ozkan, Dogus; Yilmaz, Mustafa Alper; Karakurt, Deniz; Szala, Miroslaw; Walczak, Mariusz; Bakdemir, Seda Atas; Turkuz, Cenk; Sulukan, Egemen (MDPI, 2023)
Moving components of industrial machines and tools are subjected to wear and friction. This reduces their useful life and efficiency in running conditions, particularly at high temperatures. One of the most popular solutions is to apply an appropriate surface coating to the tribocouple's base materials. In this study, tribometer experiments were used to evaluate the tribological performance of cathodic arc physical vapor deposited (CAPVD) AlCrN, TiSiN, CrTiN, and ZrN coatings on the gas nitrided AISI H13 tool steel to explore the effects of nitriding the steel on wear and friction behavior of these coatings at ambient and elevated temperatures. The coatings characterization is split into three main parts: mechanical, morphological, and chemical characterization. Nanoindentation has been used for mechanical characterization, thin film X-ray diffraction (XRD), and an energy-dispersive X-ray spectrometer mounted on a scanning electron microscope for chemical characterization, optical profilometer, and atomic force microscopy (AFM) for morphological characterization. Significant improvements in the adhesion qualities of the coatings to the substrate were achieved as a result of nitration. Due to this circumstance, the coatings' load-bearing capacity and high-temperature wear resistance ratings were enhanced. The wear results showed that the AISI H13 tool steel nitriding with AlCrN and ZrN layers decreased wear rates by two to three times at 700 degrees C.
Keywords: nitriding; H13 steel; arc-PVD; coatings; nanoindentation; high temperature wear; friction; tribology; MECHANICAL-PROPERTIES; TOOL STEEL; TRIBOLOGICAL BEHAVIOR; OXIDATION BEHAVIOR; RAMAN-SPECTROSCOPY; ZIRCONIUM NITRIDE; THIN-FILMS; RESISTANCE; TIN; ADHESION; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics